2008
DOI: 10.1016/j.brat.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of conditioned fear-potentiated startle in humans: Experimental validation and clinical relevance

Abstract: Though generalization of conditioned fear has been implicated as a central feature of pathological anxiety, surprisingly little is known about the psychobiology of this learning phenomenon in humans. Whereas animal work has frequently applied methods to examine generalization gradients to study the gradual weakening of the conditioned-fear response as the test stimulus increasingly differs from the conditioned stimulus (CS), to our knowledge no psychobiological studies of such gradients have been conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
390
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(427 citation statements)
references
References 35 publications
34
390
0
3
Order By: Relevance
“…empirical demonstrations of perceptual generalization gradients Contemporary generalization research in humans has been inspired by conditioning-based models of clinical anxiety (e.g., Lissek et al, 2008, Vervliet, Kindt, Vansteenwegen, & Hermans, 2010b. In the first contemporary systematic examination of fear generalization gradients in humans, Lissek et al (2008) showed gradients of the eye-blink startle reflex to rings that varied in size from a ring paired with shock (CS+).…”
Section: Perceptual Fear Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…empirical demonstrations of perceptual generalization gradients Contemporary generalization research in humans has been inspired by conditioning-based models of clinical anxiety (e.g., Lissek et al, 2008, Vervliet, Kindt, Vansteenwegen, & Hermans, 2010b. In the first contemporary systematic examination of fear generalization gradients in humans, Lissek et al (2008) showed gradients of the eye-blink startle reflex to rings that varied in size from a ring paired with shock (CS+).…”
Section: Perceptual Fear Generalizationmentioning
confidence: 99%
“…This generalization of conditioned fear shows that CRs are often elicited by stimuli not associated with the aversive event but which resemble the CS along a formal, perceptual dimension (Honig & Urcuioli, 1981). The study of stimulus generalization processes like this has a long history of research in both Pavlovian and instrumental/operant conditioning (e.g., Hull, 1943;McLaren & Mackintosh, 2002;Pavlov, 1927), but has only recently been extended to fear generalization in humans (Dunsmoor, Mitroff, & LaBar, 2009;Lissek et al, 2008Lissek et al, , 2010Vervliet, Vansteenwegen, Baeyens, Hermans, & Eelen, 2005;Vervliet, Vansteenwegen, & Eelen, 2004).…”
mentioning
confidence: 92%
“…Generalization is the tendency to exhibit a conditioned response to a stimulus that resembles a conditioned stimulus (CS+), in this case a symptom trigger along a perceptual dimension such as size, shape or color (Lissek et al, 2008;Riccio, Ackil, & Burch-Vernon, 1992). The strength of the response tends to decline as the resemblance between the stimulus and the CS+ decreases (Riccio et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fear-conditioning literature (e.g., Lissek et al, 2008;Vervliet et al, 2004Vervliet et al, , 2011Vervliet et al, , 2006 and models of human categorization learning (e.g., Nosofsky, 1984Nosofsky, , 1986Nosofsky, , 1986Medin & Schaffer, 1978), we hypothesized that attitude generalization is critically dependent upon FSAA. To test this hypothesis, we conducted three EC experiments and examined whether EC effects generalized to novel stimuli as a function of FSAA.…”
Section: Discussionmentioning
confidence: 99%
“…A first line of research concerns the vast amount of fear-conditioning studies showing that the generalization of conditioned fear is highly dependent upon the similarity between a novel stimulus and a known entity. Consider, for example, the findings of Lissek et al (2008). They presented participants with 10 rings of gradually increasing size with one of the extremes serving as a predictor (CS) of a highly uncomfortable electric shock (US).…”
mentioning
confidence: 99%